2010
DOI: 10.1021/jp106113h
|View full text |Cite
|
Sign up to set email alerts
|

The Intramolecular Charge Transfer State in Carbonyl-Containing Polyenes and Carotenoids

Abstract: Numerous femtosecond time-resolved optical spectroscopic experiments have reported that the lifetime of the low-lying S1 state of carbonyl-containing polyenes and carotenoids decreases with increasing solvent polarity. The effect becomes even more pronounced as the number of double bonds in the conjugated π-electron system decreases. The effect has been attributed to an intramolecular charge transfer (ICT) state coupled to S1, but it is still not clear what the precise molecular nature of this state is, and ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
120
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(128 citation statements)
references
References 68 publications
8
120
0
Order By: Relevance
“…Although it is possible to separate the S 1 -like and ICTlike transitions in transient absorption spectra, the S 1 and ICT states of carbonyl carotenoids are strongly coupled in the S 1 ∕ICT state (32,35), and the intensity of the ICT-like transition is a measure of a degree of charge-transfer character of the S 1 ∕ICT state. It was recently shown that the intensity of the ICTlike transition significantly increases if a single conjugated carbonyl group of a carotenoid is positioned in an s-trans configuration with respect to the main conjugated backbone (36); however, this is not the case for spheroidenone in solution where the carbonyl group is in an s-cis orientation as evidenced by molecular modeling showing that s-cis configuration is far more stable (Fig. S2).…”
Section: Resultsmentioning
confidence: 97%
“…Although it is possible to separate the S 1 -like and ICTlike transitions in transient absorption spectra, the S 1 and ICT states of carbonyl carotenoids are strongly coupled in the S 1 ∕ICT state (32,35), and the intensity of the ICT-like transition is a measure of a degree of charge-transfer character of the S 1 ∕ICT state. It was recently shown that the intensity of the ICTlike transition significantly increases if a single conjugated carbonyl group of a carotenoid is positioned in an s-trans configuration with respect to the main conjugated backbone (36); however, this is not the case for spheroidenone in solution where the carbonyl group is in an s-cis orientation as evidenced by molecular modeling showing that s-cis configuration is far more stable (Fig. S2).…”
Section: Resultsmentioning
confidence: 97%
“…[221] An intramolecular charge transfer (ICT) state arising in carbonyl carotenoids has been reported, for example, in refs. [222,[224][225][226]. Most studies investigating this ICT state were performed on peridinin in solution or embedded in the PCP.…”
Section: Charge-transfer States In Carbonyl-containing Carotenoidsmentioning
confidence: 99%
“…[229] Later studies suggested a coupling between the ICT and the S 1 state. [219,230] But also an S 1 state with charge-transfer character [231] and a mixed S 1 -S 2 state with rather high dipole moment [226] were suggested. Besides this S 1 -ICT mixing, an additional coupling of the resulting state with the S 2 state was supported by semi-empirical (MNDO) calculations, such that this state acquires significant B u + character.…”
Section: Charge-transfer States In Carbonyl-containing Carotenoidsmentioning
confidence: 99%
“…9,11,[15][16][17][18][19] Peridinin is a highly substituted carotenoid, with an unusually short carbon skeleton (C 37 instead of C 40 ) compared to the majority of carotenoids occurring in photosynthetic systems, whose spectroscopic properties are influenced by the presence of carbonyl groups and, possibly, of other substituents also present in its polyene chain, like an allene group. The excited state properties of carotenoids are in fact mainly determined by the structure and functionalization of their conjugated polyene chain.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,10,16,21 Although it is commonly accepted that the shortening of peridinin excited state lifetime is ascribable to the occurrence of the ICT state, the exact electronic nature and formation mechanism of ICT are still debated. 9,10,15,22,23 The presence of the carbonyl group, primarily responsible for setting up and stabilizing the charge transferred electronic structure, has a great influence on both the stationary and transient absorption spectra of peridinin. In the ground state absorption spectrum, the clear vibronic progression observed in non-polar solvents is smeared out in polar media, where the absorption band broadens and shifts to the red.…”
Section: Introductionmentioning
confidence: 99%